The production and properties of fly ash containing aluminum matrix composite materials - Kolukisa, S; Topuz, A; Sagin, A (CARL HANSER VERLAG, 2003)
Cost saving in composite materials is very important. Therefore fly ash particles, which are a waste product of coal combustion, can be used as reinforcement in aluminum matrix composite materials. Aluminum matrix composite materials (AMC) fabricated from A360 and 443 aluminum alloys and Tuncbilek, Yatagan fly ashes were used as reinforcement with volume fractions 5%, 10%, 15%, 20%. Stir mixing and casting process were used for the production of fly ash containing aluminum-matrix composites (AMC's). Specially designed and ceramic covered mixers were used for stirring of melted aluminum alloy at 750, 850, 950degreesC temperatures and 400, 560, 750 rpm rotation rates. It has been observed that, with applied production process, maximum 20% (volume fraction) fly ash can be added to aluminum alloy matrix. Referring to the experimental data, optimum properties were achieved at 850degreesC stirring temperature and 560 rpm mixer rotation rates.
Keywords: Metallurgy & Metallurgical Engineering